RESPON LEMBAGA SATUAN PENDIDIKAN DASAR NEGERI ATAS KEBIJAKAN PROGRAM WAJIB BELAJAR PENDIDIKAN DINIYAH DI KABUPATEN SUMENEP - Shiddiq, Ahmad; Asmoni (Badan Perencanaan Pembangunan Kota Malang, 2019)
Sumenep, as one of the regencies that has a majority Muslim population, is evidence that the Sumenep community is very thick with religious values. This becomes lame if Sumenep conducts the education process without the process of religious education. The mandatory diniyah program organized by the Sumenep Regency Government, with the issuance of the Sumenep Regent's Regulation, Number: 15 of 2016, concerning Compulsory Education for Early Education became the flagship program in implementing education for Sumenep students. This Mandatory Diniyah Program, that with the promulgation of the Sumenep Regent's Regulation, responding July 18, 2016, Education Unit (SD / SDLB / Pursuing Package A, SMP / SMPLB / Pursuing Package B, SMA / SMK / SMALB / SMKLB / Pursuing Package C, in Sumenep Regency MUST conduct a Mandatory Diniyah program by including it in the Education Unit Level Curriculum This research uses two methodological approaches, namely: First, library reseach (library research), used to facilitate the running of literature-based research, especially on conceptual studies and legal basis for compulsory policy diniyah and Second, field research as a way to obtain compulsory implementation of diniyah data in the sub-district of Sumenep city as a pilot project.These two approaches are carried out because the research to be carried out requires that two approaches be used so that this research becomes holistic and integrative. The response of educational unit institutions to the waj program b diniyah of Sumenep Regency in the District of Sumenep City there are two models for implementing the program. First, the partner model. In this partner model educational units, such as elementary schools collaborate with existing Madrasah Diniyah. Second, the standalone model. The independent model referred to here is that schools implement their own mandatory diniyah by establishing their own madrasa diniyah.